Mapping actors along value chains: integrating visual network research and participatory statistics into value chain analysis - Stein, C.; Barron, Jennie (International Water Management Institute, 2017)
This report outlines a participatory approach for mapping actors along value chains. The methodology provides novel ideas on how to combine value chain analysis with participatory statistics and visual network research approaches, to generate valuable insights about complex value chains together with local stakeholders in a cost effective way. A framework is introduced, which provides a canvas for mapping actors onto different analytical dimensions relevant in value chain analysis. After outlining some of the conceptual foundations and the methodological approach, a sequence of steps for mapping actors and their relationships is described. The experience from a case study is used to illustrate the steps involved. The case study is on fodder value chains in the Sahelian agro-ecological zone of Burkina Faso, but the mapping approach can be adapted to a range of contexts.